Fetal Myocardial Performance Index in the Third Trimester of Pregnancy: Feasibility and Reproducibility of Conventional Spectral Doppler versus Spectral Tissue Doppler Technique - Porche, Lea M.; Sinkovskaya, Elena; Seaman, Rachel D.; Galadima, Hadiza; Romary, Letty; Philips, Jennifer; Abuhamad, Alfred (American Journal of Perinatology, 2019)
Objective This study aims to compare completion rates and reproducibility of myocardial performance index (MPI) using conventional spectral Doppler versus tissue Doppler in an unselected high-risk third trimester population.Study Design This was a prospective cross-sectional study of high-risk pregnancies at ≥28 + 0 weeks’ gestation. Conventional spectral and tissue Doppler MPI of the left ventricle (LV) and right ventricle (RV) was attempted on all patients.Results Seventy-nine pregnancies were evaluated. LV tissue Doppler MPI was completed more frequently than LV conventional spectral Doppler MPI (63/79, 79.7% vs. 45/79, 55.7%), p-value <0.01. RV tissue Doppler MPI was completed more frequently than RV conventional spectral Doppler MPI (68/79, 86% vs. 42/79, 53.2%), p-value <0.01. In obese subjects (n = 50) LV tissue Doppler MPI was completed more frequently than LV conventional spectral Doppler MPI (37/50, 74% vs. 26/50, 52%), p-value <0.01. RV tissue Doppler MPI was completed more frequently than RV conventional spectral Doppler MPI (40/50, 80% vs. 25/50, 50%), p-value <0.01. intraclass correlation coefficient for all modalities ranged between 0.73 and 0.93, except for LV conventional spectral Doppler intraobserver variability which was 0.22.Conclusion Tissue Doppler had statistically higher completion rates than conventional spectral Doppler, including the obese subgroup, with evidence of strong reproducibility in the third trimester.
Keywords: myocardial performance index; cardiac function; tissue Doppler; spectral Doppler; third trimester